2008
DOI: 10.1007/s00284-008-9259-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Inoculum Size on Carbapenem Susceptibilities of β-Lactamase-Negative, Ampicillin-Resistant Haemophilus influenzae

Abstract: A higher inoculum size of beta-lactamase-positive Haemophilus influenzae is reported to increase minimum inhibitory concentrations (MICs) for beta-lactams. However, the effect of inoculum size of beta-lactamase-negative, ampicillin-resistant H. influenzae (BLNAR) on MICs for carbapenems has not been investigated. This study evaluated the effect of inoculum size on MICs for carbapenems and other beta-lactams in nine clinical isolates of BLNAR. The MICs were determined by both the standard method described by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…For example, aminopenicillins displayed an in vitro inoculum effect against b-lactamase-producing isolates of H. influenzae and also b-lactamase-deficient isolates of H. influenzae that were resistant to ampicillin. 92 The in vitro inoculum effect mediated by the b-lactamase-deficient isolates of H. influenzae was likely due to mutations in the protein targets of the aminopenicillins. Increasing the density of bacteria in an in vitro system will also likely decrease the average number of b-lactam molecules available to interact with a bacterial cell.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, aminopenicillins displayed an in vitro inoculum effect against b-lactamase-producing isolates of H. influenzae and also b-lactamase-deficient isolates of H. influenzae that were resistant to ampicillin. 92 The in vitro inoculum effect mediated by the b-lactamase-deficient isolates of H. influenzae was likely due to mutations in the protein targets of the aminopenicillins. Increasing the density of bacteria in an in vitro system will also likely decrease the average number of b-lactam molecules available to interact with a bacterial cell.…”
Section: Discussionmentioning
confidence: 99%
“…The inoculum effect of b-lactams against H. influenzae has been studied exclusively in the context of in vitro susceptibility testing or time-kill analyses. Substantial in vitro inoculum effects were noted for aminopenicillins [82][83][84][85][86][87] and cephalosporins, 81,84,86,[88][89][90][91] whereas carbapenems 87,92 and cefoxitin 88 were only evaluated in a few studies and did not demonstrate a substantial inoculum effect in vitro (Table 4). Two studies detected an in vitro inoculum effect for aminopenicillins against b-lactamase-producing strains of H. influenzae but did not observe an inoculum effect in b-lactamase-deficient strains.…”
Section: H Influenzaementioning
confidence: 99%
See 1 more Smart Citation
“…However, accurate susceptibility testing for these compounds, which is known to be essential for therapeutic management, is still problematic in routine clinical microbiology laboratories. It has been reported that polymyxin MICs may not be reproducible and that many factors influence its determination, such as the inoculum and the cation concentration content of the Mueller-Hinton medium (2,14,22,24). In addition, it has been observed that MICs obtained by agar dilution and Etest methods are higher than those obtained by the reference broth microdilution technique (17).…”
Section: Discussionmentioning
confidence: 81%
“…However, both of ours and Kim’s studies revealed that carbapenemase-producing K. pneumoniae isolates exhibited a higher rate of ATM-AVI inoculum effect than E. coli . In the literature, variations in PBP3 enzymes and carbapenemase activity, or the production of other β-lactamases among different species of Enterobacteriaceae might all affect the magnitude of inoculum effect ( 14 , 34 , 35 ). The presence of inoculum effects suggested potential benefits of higher doses or combination therapy to combat CPE infections with high bacterial burden.…”
Section: Discussionmentioning
confidence: 99%